2020
DOI: 10.1029/2020gl087354
|View full text |Cite
|
Sign up to set email alerts
|

El Niño Diversity Across Boreal Spring Predictability Barrier

Abstract: El Niño exerts widespread hydroclimate impacts during boreal summer. However, the current prediction of El Niño across boreal spring has the most severe forecast errors, partially due to the lack of understanding diversified El Niño onset and decay. Here we show, through nonlinear k‐means cluster analysis of evolutions of 40 El Niño events since 1870, El Niño exhibits complex and diverse flavors in its onset and decay across boreal spring predictability barrier. We detected three types of El Niño onset and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…The TCDa_G index, however, does not pass the significance test, meaning that it might be not an effective factor on affecting the ENSO variations over the whole period 1980-2018. Recently, Wang et al (2020) also found that simply using SST and zonal winds before April can successfully predict different types of El Niño, which is consistent with our viewpoint. Besides, the experiment with the preceding ENSO signal removed from the original variables is also conducted, the result of which is nearly identical with Fig.…”
Section: Connection Between the March Information And The Following Esupporting
confidence: 91%
“…The TCDa_G index, however, does not pass the significance test, meaning that it might be not an effective factor on affecting the ENSO variations over the whole period 1980-2018. Recently, Wang et al (2020) also found that simply using SST and zonal winds before April can successfully predict different types of El Niño, which is consistent with our viewpoint. Besides, the experiment with the preceding ENSO signal removed from the original variables is also conducted, the result of which is nearly identical with Fig.…”
Section: Connection Between the March Information And The Following Esupporting
confidence: 91%
“…Hereafter, any month in ENSO onset and decay year is denoted by the suffix (0) and (1), respectively. Consistent with Wang et al (2019) and Wang et al (2020a), an El Niño (La Niña) year is identified as that the Niño3.4 index during October-November-December(0)-January-February( 1) is greater (less) than or equals to 0.6 °C (−0.5 °C). As a result, 33 El Niño cases and 36 La Niña cases are identified.…”
Section: Methodssupporting
confidence: 79%
“…Pronounced CEP cooling and western Pacific warming are observed in PC1-regressed SST anomalies, and the PC1-related NWPAC is a direct Rossby wave response to CEP cooling (Figure 1B; Fan et al, 2013;Wang et al, 2013;, Above study is analyzed from the perspective of circulation diversity, and the following analysis is conducted from the perspective of SST diversity to further confirm the importance of El Niño decay pace by an objective method: nonlinear k-means cluster analysis, which is more objective than directly using the El Niño decay rate with some subjective criterions. The 33 El Niño cases can be divided into four categories by a nonlinear k-means cluster analysis of the equatorial SST anomalies averaged between 5 °S and 5 °N over the Pacific from October(0) to October(1), following Wang et al (2020a). The results of k-means cluster analysis depend on the number, k, of clusters chosen.…”
Section: Diverse Enso Decay Pacementioning
confidence: 99%
See 1 more Smart Citation
“…Based on this criterion, the two types of El Niño events that were determined using detrended monthly HadISST from 1891-2020 are as follows: • CT El Niño: 1896, 1899, 1902, 1905, 1911, 1913, 1918, 1925, 1930, 1940, 1941, 1951, 1957, 1965, 1972, 1976, 1982, 1986, 1991, 1997• WP El Niño: 1900, 1940, 1941, 1957, 1958, 1968, 1977, 1986, 1987, 1990, 1991, 1992, 1993, 1994, 2002, 2004, 2006, 2014 It can be seen that several events (1940,1941,1957,1986,1991,2009,2015) are defined as both CT and WP El Niño events based on this determination criterion, which is due to the fact that these events show significant warming in both Niño3 and Niño4 regions and are basin-wide warm events. Therefore, some studies also refer to these events as "strong basin-wide" events and do not regard them as a regular CT or WP El Niño (Wang et al, 2019;Wang et al, 2020). In following analyses, we still keep these events in their respective categories.…”
Section: Precipitation Anomaly Patterns Associated With Two Types Of ...mentioning
confidence: 99%